Mediating effect of self-efficacy on relationship between selected variables and employability among university students in north-eastern Nigeria - Wujema, Baba Kachalla (2021)
University education is assumed to be the key element of human resource development. Hitherto, the present education system in Nigeria is well known for its inability of producing graduates with essential and generic skills; henceforth the incessant surge in the problems of youth unemployment and graduate employability. Nigeria has one of the highest rate of unemployment figures, that is around 36% in 2019 as against 36.5% in 2018 in the world and that the graduates of Nigerian universities had the hardest hit by the menace of unemployment. Various studies had been conducted to investigate graduate employability in Nigeria with focus on the university graduates. However, studies that focuses on employability among university students are limited. The objectives of the study is to determine the level of university student’s employability in Nigeria. The objective of the study is to determine the mediating effect of self-efficacy on the relationship between selected factors (emotional intelligence, career development learning, generic skills, work experience, degree subject knowledge and understanding skills, entrepreneurial orientation and ICT acceptance) and employability among university students in (University of Maiduguri, Yobe State University Damaturu, Federal University Gashua, ATBU, Bauchi, Gombe State University and MAUTECH, Yola) North Eastern Nigeria. The study has used CareerEDGE model on employability, then self-efficacy served as the mediating variable. Additionally, two more variables were included in the CareerEDGE model and they are ICT acceptance and entrepreneurial orientation, while social cognitive theory and self-regulation theory served as their theories. The present study employed a quantitative approach with correlational research design. In addition, it adopted a cross-sectional survey using structured questionnaires in data collection. The data for this study was obtained from 264 respondents through a self-administered questionnaire. Undergraduate students in North Eastern Nigeria were ii selected through a simple random sampling procedure from a total population of 2109. Six (6) universities in North Eastern Nigeria were selected for the study. The descriptive analysis part deals with the respondent's responses, and this was done with IBM SPSS version 23 software, while inferential analysis was employed to determine the relationships between the independent variables and dependent variable, the mediating role of self-efficacy in the relationship, and whether the predictor variables can significantly predict undergraduate students’ employability. To achieve this, Structural Equation Modelling (SEM) using Analysis of Moment Structures (AMOS) software was employed to analyse the data. Interestingly, the study has revealed that perceived usefulness, risk taking, innovativeness and proactiveness have a significant influence on employability among undergraduate students of universities in North-Eastern Nigeria. Further, it showed that emotional intelligence, generic skills and degree subject knowledge and understanding skills have a significant influence on employability among undergraduate students in North Eastern Nigeria. As a whole, the study found that career development learning is the factor that enables undergraduate students to make career decisions which greatly influences their employability. However, the mediation test revealed that, self-efficacy mediates relationship with work experience, while other variables did not mediate the relationship with self-efficacy. The implications of this study is that university students in Nigeria will need to have the knowledge, skills, technical skills, technological know-how, as well as communication skills, and a good understanding of their career skills, because that will in no small measure ameliorate their likelihoods of getting employment in the Nigerian labour market. Based on the findings, it was suggested that government should also resuscitate the National Directorate of Employment (NDE) and Poverty Eradication Programme (PEP), so that they should provide training opportunities to our jobless graduates which will enable them to be employable in the labour market. Future studies should also include other parts of CareerEDGE model which the present study has not included, they include; self-esteem, self-confidence and reflection and evaluation. Therefore, including other components of CareerEDGE model would give wider coverage in understanding employability among university students.